2021
DOI: 10.1038/s41598-021-85307-1
|View full text |Cite
|
Sign up to set email alerts
|

Knee-related disability was largely influenced by cognitive factors and disturbed body perception in knee osteoarthritis

Abstract: The aim of this study was to explore the existence of subgroups in a cohort of people with knee osteoarthritis (OA) based upon data from multiple pain-related variables and to profile identified clusters according to levels of pain intensity and knee-related disability. Three hundred and three people with knee OA were recruited. Latent profile analysis was used to confirm the optimal number of knee OA subgroups. Body mass index, radiographic knee OA severity, pain catastrophizing, pain related self-efficacy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…Many of these studies considered various combination of clinical characteristics only including but not limited to BMI, radiographic scores, pain metrics, bone mineral density, magnetic resonance imaging (MRI) score, Hb-A1C, cholesterol, depression symptoms, serum, and urine biomarkers. 8 , 9 , 27 - 29 Similar to our findings, some of these studies also found KL radiographic score and BMI as characteristics that can be used to discriminate OA subgroups. 8 , 27 , 28 Few other studies focused on the RNA sequencing and metabolic profiling of cartilage and SYN to identify OA subgroups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Many of these studies considered various combination of clinical characteristics only including but not limited to BMI, radiographic scores, pain metrics, bone mineral density, magnetic resonance imaging (MRI) score, Hb-A1C, cholesterol, depression symptoms, serum, and urine biomarkers. 8 , 9 , 27 - 29 Similar to our findings, some of these studies also found KL radiographic score and BMI as characteristics that can be used to discriminate OA subgroups. 8 , 27 , 28 Few other studies focused on the RNA sequencing and metabolic profiling of cartilage and SYN to identify OA subgroups.…”
Section: Discussionsupporting
confidence: 90%
“… 8 , 9 , 27 - 29 Similar to our findings, some of these studies also found KL radiographic score and BMI as characteristics that can be used to discriminate OA subgroups. 8 , 27 , 28 Few other studies focused on the RNA sequencing and metabolic profiling of cartilage and SYN to identify OA subgroups. 6 , 7 , 10 , 11 , 30 These studies have reported cartilage extracellular matrix genes (GAG) and collagen-associated genes to discriminate OA subgroups.…”
Section: Discussionsupporting
confidence: 90%
“… 54 Furthermore, cluster analysis suggests that disrupted knee perception may explain some of the discrepancy between knee pain–related disability and severity of radiographic findings in knee OA. 37 Item 7 of the FreKAQ (back translated from Japanese: I feel like my knee is bigger [swollen]), specifically asks about knee size and the difference between perception and reality. We found that this item was significantly easier to endorse for people with knee OA than the similarly worded item was for people with low back pain, 35 neck pain, 63 or shoulder pain, 38 which suggests this issue might be particularly relevant in knee OA.…”
Section: Introductionmentioning
confidence: 99%
“…Because of osteoarthritis, over 100,000 persons in the United States are unable to walk from their bedroom to their bathroom due to reduced muscle strength, disturbed body perception and joint dysfunction. 5,6,7 Imbalance between the muscles may arise when a person have tight hip joint musculature which ultimately leads to injury. Due to the hip flexors and quadriceps overworking to compensate for weak muscles it may frequently causes fatigue and reduction in strength eventually cause knee and hip pain.…”
Section: Introductionmentioning
confidence: 99%